The Effect of Tax Avoidance on The Cost of Debt with Tax Risk as A Moderating Variable - Syafira, Yustin Septa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study examines the effect of tax avoidance on the cost of debt with tax risk as a moderating variable titled “The Effect of Tax Avoidance on The Cost of Debt with Tax Risk as A Moderating Variable”. The data examined in this research comes from secondary data in the form of financial reports presented by the company. The companies that will be researched are infrastructure, transportation & logistics, property & real estate, and technology listed on the IDX for the 2019-2022 period listed on the IDX. Based on the object of this research, a total of 104 financial reports are observation data. This research uses the Descriptive Statistics Test, the Classical Assumption Test and the Multicollinearity Test as stages to test the normality of the data. Then, there is multiple linear analysis, which is continued with the Coefficient of Determination Test and ends with hypothesis testing via the T and F tests. The results obtained are tax. Avoidance positively affects the cost of debt, so tax risk weakens the interaction of tax avoidance with the cost of debt.